JORDAN SMALL AND MEDIUM SCALE INDUSTRIES 2000-2010: PERIODICAL EVALUATION - Jaber Mohammed Al-Bdour (European Scientific Journal, ESJ, 2013)
The role of the industrial sector in the Jordanian economy is increasing year by year. Its share of GDP accounted for 23% in 2011 compared with 22% in 2007. In this sector, the debate always has been on its source of growth. Was the source of growth in this sector small scale or large scale industries? Many policy measures have also been adopted to encourage investment in the industrial sector. Those measures were biased towards large scale industries. This is reflected by the creation of industrial city zones in various parts of the country, as well as in the encouragement of investment laws.This empirical research will answer the following questions; which was more successful small scale industries or large scale industries? Which was more successful labor intensive or capital intensive industries? Which were more successful private ownership industries or public ownership?To provide answers to the previous questions, Jordan experience will be evaluated in light of the following:1- Profit maximization is the prime goal of any investor, and the question is; which industries achieved higher profits, the small or larger scale industries?2- The efficiency of any industry can be measured, in addition to its profitability, by its productivity level which is considered the source of profitability.3- Capital intensive industries believed to be more productive than labor intensive industries. Therefore, the analyses will take these intensities into consideration when evaluating profitability and productivity levels.Evaluating the previous three indicators (profitability, productivity, and capital and labor intensities, on the industry level not firm level), will be carried out to show the degree of success of S&M industries in comparison with large scale industries prior and after the financial crisis of 2008.This research concluded that small and medium scale industries were more successful than large scale industries.